2014
DOI: 10.1186/2193-1801-3-88
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of non-genetic factors affecting milk yield and composition of Red Dane and Jersey cattle in Zimbabwe

Abstract: A study was carried out to evaluate non genetic factors affecting milk yield and milk composition in Zimbabwean Red Dane and Jersey cattle cattle. A total of 1004 and 10 986 unedited Red Dane and Jersey 305-day lactation records respectively, were obtained from Livestock Identification Trust (LIT) containing 22 herds (1 Red Dane herd and 21 Jersey herds), with Red Dane calving in the period 2004 to 2009 (giving year of birth from 1998 to 2007) and Jersey cows calving in the period 1996 to 2008 (giving year of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 8 publications
3
16
0
Order By: Relevance
“…On perusal of Table 2, it is evident that animals in third and fourth parities produced comparatively more total milk per day of lactation length and total milk per day of calving interval as compared to animals of earlier and later parities. This suggests that milk yield increases as parity proceeds because due to large body size and increased development of udder tissue large cows produce more milk than cows of earlier parities/heifer (Nyamushamba et al, 2014). The milk yield was also lower in early parities because the energy derived from feed that was provided to the heifers was also channeled to their growth.…”
Section: Resultsmentioning
confidence: 99%
“…On perusal of Table 2, it is evident that animals in third and fourth parities produced comparatively more total milk per day of lactation length and total milk per day of calving interval as compared to animals of earlier and later parities. This suggests that milk yield increases as parity proceeds because due to large body size and increased development of udder tissue large cows produce more milk than cows of earlier parities/heifer (Nyamushamba et al, 2014). The milk yield was also lower in early parities because the energy derived from feed that was provided to the heifers was also channeled to their growth.…”
Section: Resultsmentioning
confidence: 99%
“…Higher milk fat and protein contents in primiparous cows were connected with the lower milk yield; when the limiting milk yield associated with the growth of mammary gland and promotes a higher fat and protein contents in milk [21].…”
Section: Discussionmentioning
confidence: 98%
“…The lactation order is associated with the age of the cows. When the primiparous cows use nutrients from TMR for full development of tissues of the mammary gland and body frame, the milk synthesis is limited [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parity and season had no effect on cholesterol, magnesium and phosphorus. A study by Nyamushamba et al, (2014) [10], indicated that parity, year of calving, days in milk and age of calving affect yield and composition of milk of Red Dane cows in Zimbabwe. It was reported by Sutthisak et al, (2014) [11], that milk protein and SNF were found to be higher during rainy season than in the summer and winter seasons.…”
Section: Introductionmentioning
confidence: 99%